2008
DOI: 10.1534/genetics.107.085282
|View full text |Cite
|
Sign up to set email alerts
|

High DNA Sequence Diversity in Pericentromeric Genes of the Plant Arabidopsis lyrata

Abstract: Differences in neutral diversity at different loci are predicted to arise due to differences in mutation rates and from the ''hitchhiking'' effects of natural selection. Consistent with hitchhiking models, Drosophila melanogaster chromosome regions with very low recombination have unusually low nucleotide diversity. We compared levels of diversity from five pericentromeric regions with regions of normal recombination in Arabidopsis lyrata, an outcrossing close relative of the highly selfing A. thaliana. In con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
12
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 78 publications
6
12
0
Order By: Relevance
“…Moreover, the lack of an effect for self-compatibility in our estimates of N e for Arabidopsis may be not surprising as selfcompatibility might evolved relatively recently in Arabidopsis (Bechsgaard et al 2006;Tang et al 2007). Furthermore, both Arabidopsis species have high sequence diversity in pericentromeric regions (Borevitz et al 2007;Kawabe et al 2008) that is not caused by varying mutation rates. Therefore this could be a major determinant of variation in N e in those species and interfere with the effects of the breeding system.…”
Section: Discussionmentioning
confidence: 85%
“…Moreover, the lack of an effect for self-compatibility in our estimates of N e for Arabidopsis may be not surprising as selfcompatibility might evolved relatively recently in Arabidopsis (Bechsgaard et al 2006;Tang et al 2007). Furthermore, both Arabidopsis species have high sequence diversity in pericentromeric regions (Borevitz et al 2007;Kawabe et al 2008) that is not caused by varying mutation rates. Therefore this could be a major determinant of variation in N e in those species and interfere with the effects of the breeding system.…”
Section: Discussionmentioning
confidence: 85%
“…Roselius et al (2005) found a significant relation between diversity levels and recombination rate in wild tomato species. Nordborg et al (2005) and Kawabe et al (2008) found a negative association between gene density and diversity levels in A. thaliana and A. lyrata, respectively, as did Flowers et al (2012) in rice; given the positive correlation between recombination rate and gene density, this tends to obscure any effect of recombination rate. Positive correlations between recombination rate and putatively neutral diversity have also been reported in budding yeast (Cutter and Moses 2011) and chickens (Rao et al 2011).…”
Section: Recombination Rate and Bgsmentioning
confidence: 93%
“…In many taxa, there is a positive correlation between intrapopulation diversity and genomically local recombination rates (3). In A. thaliana (16,17) and the outbred A. lyrata (31), there is, unusually, high sequence diversity near centromeres. This has been considered contrary to classical theory as centromeres were assumed to have low CO rates, and thus prone to weak HillRobertson interference reducing diversity (31).…”
Section: Pericentromeric Recombination May Explain Prior Unusual Obsementioning
confidence: 99%